Comportamiento agronómico del cultivo de arroz a la aplicación de Activadores enzimáticos en diferentes dosis en la zona de la Carmela, Cantón Babahoyo - Sorroza Jiménez, Jairon Alberto (2020)
This experimental work was carried out on the grounds of the La Carmela Campus belonging to the Pimocha Parish of the Babahoyo Canton, located at Km 12 of the Babahoyo - Jujan road. The objective of this investigation was to evaluate the agronomic behavior of rice with Zerebra application at different doses and epcosa of application, and its influence on the development and yield of the crop. Rice sowing was done with the INIAP14 variety in plots of 16 m2. Treatments were distributed in a randomized complete block design. For the evaluation of means, the Tukey test was used at 5% significance. At the end of the crop cycle, plant height, number of tillers per m2, grains per panicle, length and number of panicles m2, days to flowering, days to harvest, number of grains per panicle, weight 1000 seeds and yield per hectare were evaluated. . The results determined that the agronomic characteristics of plant height, number of tillers and panicles / m2, length of panicle and grains per panicle showed good results applying the treatments. The highest yield was presented with the application of Zerebra® 0.2 + fertilizer at 15, 25 and 35 days after sowing. Zerebra® 0.2 + fertilizer at 15, 25 and 35 days after sowing showed the highest profit and net benefit.